Evaluasi Pelaksanaan Pembelajaran Jarak Jauh pada Masa Pandemi Covid-19 di SMP Negeri 2 Kupang Barat - Novi Dafa; Denny Tewu (Journal on Education, 2023)
Distance learning is an online-based learning strategy that utilizes web platforms. This distance learning model begins with thorough and well-directed planning and employs appropriate teaching methods in selecting suitable learning media, resulting in effective and successful learning outcomes. The issue addressed in this study is how to design the implementation of distance learning at SMPN 2 Kupang Barat. The qualitative method was utilized in this research, with three teachers and 60 students from 8th grade as the subjects. The data analysis technique employed was descriptive analysis. The research findings revealed that distance learning at SMPN 2 Kupang Barat is conducted using two methods: online learning (daring) and limited face-to-face interactions (luring). The purpose of using the luring method is to accommodate students who lack internet access or Android devices. However, the implementation of distance learning encounters several obstacles that hinder its progress. One of the challenges identified is the suboptimal design of distance learning by teachers. They face difficulties in designing learning activities that align with the COVID-19 pandemic conditions and the recommended curriculum set by the government. Consequently, the instructional design prepared by the teachers falls short of expectations and fails to meet the desired outcomes. Additionally, students lack the experience of experiencing the teachers' competency in designing engaging learning experiences. This negatively impacts the quality of distance learning received by the students.